The Influence of Cutting Condition on Surface Roughness in Face Milling Of Mild Steel - Salwani, Mohd Salleh; Wan Fathin, Nazirrudidin (Universiti Malaysia Pahang, 2008)
This study is aimed to determine the influence of cutting conditions such as cutting speed, feed rate and depth of cut on surface roughness in face milling of mild steel. Perthometer is being used to determine the surface roughness. Several experiments have been carried out under various cutting conditions. Roughness result shows that the surface is smoother as the cutting speed increases until it reaches the optimum speed. On the other hand cutting speed that is beyond the optimum value results in more vibration, thus generating rough surface. Meanwhile increasing the feed rate shows higher surface roughness. The depth of cut, by increasing the surface, is smoother. So the optimal value of cutting condition must be used to minimize surface roughness.